RELATIONSHIP BETWEEN TOTAL LENGTH AND GILL SURFACE AREA IN ORANGE SPOTTED GROUPER, EPINEPHELUS COIOIDES (Hamilton, 1822) - Mohammed, F. A. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2018)
The present study deals with the estimation of gill surface area for orange spotted grouper (Epinephelus coioides) collected from Iraqi marine water, north west Arabian Gulf. In the laboratory, fishes were separated in to five different length groups ranging from 200-325 mm and weight range of 108.8-582.2g. Absolute and relative total gill surface area (GSA) were estimated for 33 fish from different lengths. Statistical analysis of results revealed that there were significant differences (P<0.05) between total length of gill filaments (TFL) in different length groups, while there were no significant differences (P>0.05) between secondary lamellae (Bl) in different length groups. Statistical analysis showed also that there were significant differences (P<0.05) between secondary lamellae numbers (N) in some length groups.Statistical analysis of results showed significant differences (P<0.05) between absolute surface area of most different length groups, and also significant differences (P<0.05) between relative surface area of different length groups except group of 276-300 mm with group of 301-325 mm. Results showed positive relationship between absolute surface area and length groups with significant correlation, and negative relationship between relative surface area and length groups with significant correlation (-0.989).It seemed that the factor L had a direct effect on the values of absolute respiratory area and Fish weight had an inverse effecte on the the relative area of the gills.